DAMPAK PEMBANGUNAN JALAN KERETA API LAYANG DI RUAS PERSIMPANGAN PALANG JOGLO SURAKARTA - Sondang Kuncoro; Rachmat Mudiyono; Soedarsono (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
The Joglo intersection is a confluence of two national roads, namely Jl. Ki Mangunsarkoro and Jl. Youth Pledge. Then two provincial roads namely Jl. Colonel Sugiono who headed towards Purwodadi and Jl. Pierre Tendean. The traffic flow at the Joglo intersection is getting denser. This study aims to determine the level of service at level crossings at Joglo Crossings. Data collection was carried out by means of a direct survey at the intersection of the joglo cross section during peak hours in the morning, afternoon and evening from 06.00 - 18.00 WIB. From the survey results, grouping was carried out on each segment at the intersection and presented in the form of a vehicle table. In calculating the intersection analysis using the 1997 Indonesian Road Capacity Manual. The performance results of the Surakarta joglo intersection before construction showed that the degree of saturation in the morning was 0.612, the degree of saturation during the day was 0.474 indicating the level of class C road service. The degree of saturation in the afternoon was 0.969 indicating the level of class E road service, while the degree of saturation at construction shows the morning of 0.620, the degree of saturation during the day is 0.634 which indicates the level of class C road service. The degree of saturation in the afternoon is 1.064 which indicates the level of class F road service. In the Elevated Railway Development Project there will be narrowing on certain sections due to With this development, traffic engineering management was carried out while construction was in progress.